The Strengths and Difficulties Questionnaire (SDQ-Fin) among Finnish children and adolescents - Koskelainen, Merja (fi=Turun yliopisto|en=University of Turku|, 2008)
Objective: The psychometric properties of The Strengths and Difficulties Questionnaire (SDQ-Fin), a Finnish version of a brief screening instrument were studied. Emotional and behavioural problems of 7- to 15-year-olds measured by the SDQ were reported, as well as the occurrence of self-reported eating disturbance symptoms and alcohol use among adolescents. Methods and samples: The cross-sectional school survey included 25 items of the SDQ-Fin, items about eating disturbance, alchol use and child psychiatric help-seeking. The study consists of three community samples: 1. The SDQ-Fin parent (n = 703) and teacher (n = 376) versions of 7 – 12 –year-olds, and self-report versions (n = 528) of 11 – 16 years-olds were obtained, and 2. the parent (n = 81) and self-report versions of 15-16 –year olds (n = 129) were obtained in Laitila and Pyhäranta. 3. The self-report versions of 13 – 16 – year-olds (n = 1458) in Salo and Rovaniemi were obtained. Results: The psychometric properties of the SDQ-Fin were for the most part comparable with the other European SDQ research results. The internal consistency (Cronbach’s alpha = 0.71 in all informants’ reports) and inter-rater reliability (between the pairs of reports r = 0.38 - 0.44) were adequate. The concurrent validity (r = 0.75 between the SDQ and the CBCL total scores; r = 0.71 between the SDQ and the YSR total scores) was sufficient. Factor analysis of the SDQ self-report generally confirmed the postulated structure for girls and boys, except for the conduct problems scale of boys, which was fused with emotional symptoms and with hyperactivity. The response rates, means and cut-off points of the SDQ self-report scores were similar to those found, e.g. in Norway and in Britain. A high level of psychological problems, especially emotional and conduct problems and hyperactivity-inattention, were associated with high level of eating disturbance symptoms and alcohol use. Conclusion: The results showed that the psychometric properties of the SDQ-Fin are adequate and provide additional confirmation of the usefulness of the SDQ-Fin for, e.g. screening, epidemiological research and clinical purposes.

Tavoitteet: Vahvuudet ja vaikeudet –kyselylomake (the Strengths and Difficulties Questionnaire, SDQ-Fin) on tätä tutkimusta varten laadittu suomenkielinen käännös lyhyestä, laajalti käytetystä seulontalomakkeesta. Tutkimuksen tavoitteena oli kartoittaa SDQ-Fin -kyselylomakkeen psykometrisia ominaisuuksia, reliabiliteettia ja validiteettia suomalaisella aineistolla. Tavoitteena oli myös kuvata lomakkeen avulla kartoitettuja tunne-elämän ja käyttäytymisen ongelmia sekä tutkia näiden yhteyksiä nuorten psykososiaalisiin ongelmiin: syömisongelmiin ja alkoholinkäyttöön. Menetelmät ja otokset: Koululaiskysely sisälsi SDQ-Fin lomakkeen 25 kysymystä sekä kysymyksiä lastenpsykiatriseen hoitoon hakeutumisesta, syömisongelmista ja alkoholinkäytöstä. Tutkimus tehtiin kolmesta otoksesta: Laitilassa ja Pyhärannassa ensinnäkin 7-12 –vuotiaiden vanhemmat (n = 703) ja opettajat (n = 376) sekä 11-16 –vuotiaat nuoret itse (n = 528) täyttivät lomakkeet ja toiseksi 15-16 –vuotiaat nuoret (n = 129) ja heidän vanhempansa (n = 81) täyttivät kyselylomakkeet. Salossa ja Rovaniemellä 13-16 –vuotiaat nuoret (n = 1458) täyttivät kyselylomakkeen. Tulokset: SDQ-Fin kyselylomakkeen psykometriset ominaisuudet olivat suurelta osin vertailukelpoisia kansainvälisten tutkimusten tulosten kanssa. SDQ-Fin kokonaisongelmien asteikon sisäinen yhtenäisyys (Cronbachin alpha = 0.71), arvioitsijoiden välinen reliabiliteetti (arvioitsijaparien välillä r = 0.38 – 0.44) sekä samanaikaisvaliditeetti (kokonaisongelmien pistemäärissä SDQ-Fin ja CBCL välinen korrelaatio = 0.75; SDQ-Fin ja YSR välinen korrelaatio = 0.71) olivat riittävän hyviä. Faktorianalyysin tulokset vahvistivat tyttöjen ja poikien itse täyttämien lomakkeiden osalta oletetun rakenteen, lukuun ottamatta poikien osalta käytöshäiriön faktoria, jonka kysymykset korreloivat vahvemmin tunne-elämän ja tarkkaavaisuus ongelmien faktoreiden kanssa. Nuorten itsensä täyttämissä lomakkeissa ongelmien prevalenssi, keskiarvot ja katkaisupisteet olivat samansuuntaisia kuin esim. norjalaisissa ja brittiläisissä tutkimuksissa. Lisäksi nuorten kuvaamien ongelmien määrä, erityisesti tunne-elämän, käytöshäiriön ja tarkkaavaisuus-ongelmien määrä, korreloi syömisongelmien ja alkoholin käytön määrän kanssa. Johtopäätökset: Tutkimuksen tulokset osoittivat, että Vahvuudet ja vaikeudet –kyselylomakkeen psykometriset ominaisuudet ovat suurelta osin hyvät ja se on käyttökelpoinen menetelmä seulontaan, epidemiologiseen tutkimukseen ja kliiniseen käyttöön.
Keywords: Alcohol Drinking; Adolescent Behavior - psychology; Child Psychiatry; Child, Preschool; Adolescent; Questionnaires; Child Behavior - psychology; Eating Disorders; Adolescent Psychiatry; Adolescent Behavior - methods; Psychometrics